Monitoring dark hydrogen fermentation performance of indigenous Clostridium butyricum by hydrogenase gene expression using RT-PCR and qPCR - Wang, M.Y.; Tsai, Y.L.; Olson, B.H.; Chang, J.S.
Hydrogenase is the key enzyme responsible for H2 production in dark fermentation. Therefore, the expression of hydrogenase gene may be a good indicator for the performance of a dark H2 fermentation culture. In this study, we investigated the correlation between expression of the functional gene (hydA encoding for hydrogenase in Clostridium butyricum)and bioH2 production activity during batch growth of an indigenous H2-producing isolate C. butyricum CGS5 using sucrose as the sole carbon source. The copy number of hydA mRNA was determined by using reverse transcription PCR (RT-PCR)and quantitative PCR (qPCR). The results show that the specific hydrogen production rate of C. butyricum CGS5 was essentially linearly proportional to the level of hydA expression (represented by the copy umber of hydA cDNA), whereas the profiles of microbial growth and volumetric H2 production rate followed a similar trend to that of the hydA DNA copies.
Keywords: DARK H2 FERMENTATION; CLOSTRIDIUM BUTYRICUM; HYDROGENASE; HYDA GENE; REVERSE TRANSCRIPTION PCR (RT-PCR); QUANTITATIVE PCR (QPCR